Not only the studies – a photoreport from the activity of the “Geotourism” Special Interest Group of the Student’s Scientific Association at the AGH-UST - Birówka, Mateusz (Geotourism/Geoturystyka, 2018)
The “Geotourism” Special Interest Group of the Student’s Scientific Association at the at the Faculty of Geology, Geophysics and Environment Protection, AGH-University of Science and Technology has been active since almost 10 years.During this time the association has attracted tens of enthusiasts interested in geotourism. Recently, over twenty ambitious, hungry for knowledge colleagues are active in our group, most of them studying the Tourism & Recreation and Geology & Mining Engineering courses.